Rewriting the Metanarrative of Apartheid in the Democratic South Africa - Roya, Witness; Ngcobo, Sandiso (Research in Social Sciences and Technology, 2025)
In the aftermath of South Africa's attainment of political freedom in 1994, the country's history has been depicted through numerous literary works. Most of these works are distinguished by a 'master narrative' that conveys the notion of apartheid's overwhelming oppression, perpetuating the unrealistic perception of constant black misery. We sought texts which depart from this single narrative to encourage more studies as currently, there is little research which strikes a balance between miserable and nostalgic experiences of apartheid in several literary texts. Employing the theoretical framework of Apartheid Studies, a purposive sampling approach was employed to carefully choose four literary works that were then analyzed for their representation of the everyday experiences of black individuals. The analyses of the four texts were categorized into five overarching themes: identity, displacement, violence, betrayal, and writing as a weapon. The findings indicate that the authors adeptly capture the daily experiences of black individuals in Apartheid-era South Africa, employing humour to depict their quest for democracy. Any narrative of South Africa's history produced in the democratic era should encompass the country's achievements and shortcomings, and accurately represent its diverse makeup.